2020
DOI: 10.1002/cncr.33121
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer treatment delays by socioeconomic and health care access latent classes in Black and White women

Abstract: BACKGROUND: Breast cancer mortality is higher for Black and younger women. This study evaluated 2 possible contributors to disparities-time to treatment and treatment duration-by race and age. METHODS: Among 2841 participants with stage I-III disease in the Carolina Breast Cancer Study, we identified groups of women with similar patterns of socioeconomic status (SES), access to care, and tumor characteristics using latent class analysis. We then evaluated latent classes in association with treatment delay (ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 52 publications
3
56
0
Order By: Relevance
“…Racial inequities are found in time to diagnosis, surgery [9,10], and adjuvant chemotherapy [11,12]. Racial inequities have also been found in treatment duration; results from the Carolina Breast Cancer Study indicate that Black women experienced 1.73 times higher odds of significant delays in treatment initiation and 1.69 odds of longer treatment duration compared to White women [13]. Racial inequities in time to treatment have been linked to racial disparities in mortality [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Racial inequities are found in time to diagnosis, surgery [9,10], and adjuvant chemotherapy [11,12]. Racial inequities have also been found in treatment duration; results from the Carolina Breast Cancer Study indicate that Black women experienced 1.73 times higher odds of significant delays in treatment initiation and 1.69 odds of longer treatment duration compared to White women [13]. Racial inequities in time to treatment have been linked to racial disparities in mortality [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Our recent findings, in the Carolina Breast Cancer Study (CBCS), suggest that breast tumors of recently postpartum women were more frequently node positive and had unique immune microenvironments, but it is unknown how common treatment delay is among these women. Previous analyses from the CBCS indicated that younger (<50 years of age) women had fewer treatment delays compared to older (50-74 years of age) women [42,43], but comparisons in that study were not restricted to premenopausal women or to those with recent pregnancy. It is important to understand differences in treatment patterns for women with higher risk of aggressive cancers because delays and undertreatment are linked to worse overall and breast cancer-specific survival [44].…”
Section: Consent For Publicationmentioning
confidence: 87%
“…Access to psychosocial services is influenced by system, provider, and patient factors (Matthews et al, 2004 ) and a large body of research has documented disparities in oncology treatment and care based on various sociocultural identities, such as race (Emerson et al, 2020 ; Hardy and Du, 2021 ), SES (Dreyer et al, 2018 ; Karanth et al, 2019 ), and gender (Tabaac et al, 2018 ; Benchetrit et al, 2019 ). Access may also be subject to provider biases based on attitudes, socialized norms, as well as patients' perceived stigma around mental health services and varying communication styles and willingness to disclose emotional and psychosocial distress.…”
Section: Discussionmentioning
confidence: 99%
“…One understudied barrier to behavioral oncology care is gender/sex bias and disparities. A large body of research exists documenting disparities in oncology treatment and care based on various sociocultural identities, such as race (Emerson et al, 2020 ; Hardy and Du, 2021 ), socioeconomic status (SES) (Dreyer et al, 2018 ; Karanth et al, 2019 ), and gender (Tabaac et al, 2018 ; Benchetrit et al, 2019 ) however, less attention has been paid to sociocultural disparities, namely gender/sex disparities, in referral practices to behavioral oncology services. Given previous research documenting disparities in cancer care, and the need to increase utilization rates of behavioral oncology for cancer patients with psychosocial distress, this study aims to examine the presence of sex disparities in referral rates to psychosocial services (i.e., counseling and psychiatric services) for Adolescent and Young Adult (AYA) cancer patients.…”
Section: Introductionmentioning
confidence: 99%